2020
DOI: 10.1101/2020.03.17.994509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA sequencing of human, macaque, and mouse testes uncovers conserved and divergent features of mammalian spermatogenesis

Abstract: Spermatogenesis is a highly regulated process that produces sperm to transmit genetic information to the next generation. Although extensively studied in mice, our current understanding of primate spermatogenesis is limited to populations defined by state-specific markers defined from rodent data. As between-species differences have been reported in the process duration and cellular differentiation hierarchy, it remains unclear how molecular markers and cell states are conserved or have diverged from mice to m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 103 publications
1
19
0
Order By: Relevance
“…To get a sense of cellular interactions of Tcf21 + cells within the testis, we calculated Interaction Scores for highly variable and previously defined ligand-receptor (L-R) pairs in germ cells and somatic cells or among somatic cells of the testis (Figure 6C, Table S3). We previously showed that the Tcf21 + population has more potential interactions with spermatogonial populations than other germ cells (Shami et al, 2020) (Figure 6C, right panel), Similarly, we find that spermatogonia can convey information back to the Tcf21 + population (Figure 6C, left panel) via Pdgfa, various ADAMs, calmodulins, FGFs, and guanine nucleotide binding proteins (Table S3).…”
Section: Adult Tcf21+ Cells Contribute To Somatic Turnover In the Tessupporting
confidence: 78%
See 3 more Smart Citations
“…To get a sense of cellular interactions of Tcf21 + cells within the testis, we calculated Interaction Scores for highly variable and previously defined ligand-receptor (L-R) pairs in germ cells and somatic cells or among somatic cells of the testis (Figure 6C, Table S3). We previously showed that the Tcf21 + population has more potential interactions with spermatogonial populations than other germ cells (Shami et al, 2020) (Figure 6C, right panel), Similarly, we find that spermatogonia can convey information back to the Tcf21 + population (Figure 6C, left panel) via Pdgfa, various ADAMs, calmodulins, FGFs, and guanine nucleotide binding proteins (Table S3).…”
Section: Adult Tcf21+ Cells Contribute To Somatic Turnover In the Tessupporting
confidence: 78%
“…We recently employed single-cell RNAseq (scRNAseq) to generate a molecular atlas of the mouse testis (Green et al, 2018, Sohni et al, 2019 (Shami et al, 2020). Our analysis of 35,000 cells identified not only all somatic cell types known to be present in the adult mouse testis but also an unexpected Tcf21 + population (Figure 1A) (Green et al, 2018).…”
Section: The Tcf21 + Population Is a Mesenchymal Cell Population Thatmentioning
confidence: 94%
See 2 more Smart Citations
“… 29 Tan et al listed most of the singleā€cell transcriptome analyses that have been conducted on mouse, human, and macaque testes 30 . By modifying their report, singleā€cell transcriptome analysis performed using human testicular samples is summarized in Table 1, 31ā€“38 which included eight publications and our current project. The majority of them have focused on germ cells, and the major method to isolate and harvest a single cell type, which is the most important and difficult part of singleā€cell analysis, was enzymatic digestion combined with flow cytometric sorting or physical filtering.…”
Section: Single Cell Analysis Of Testicular Cellsmentioning
confidence: 99%